Respuesta :

Answer:

  • (-3, 4)
  • (5, 0)

=====================

Given system

  • x + 2y = 5
  • x² + y² = 25

Rearrange the first equation

  • x = 5 - 2y

Substitute the value of x into second equation

  • (5 - 2y)² + y² = 25
  • 4y² - 20y + 25 + y² = 25
  • 5y² - 20y = 0
  • y² - 4y = 0
  • y(y - 4) = 0
  • y = 0 and y = 4

Find the value of x

  • y = 0x = 5 - 2*0 = 5
  • y = 4x = 5 - 2*4 = -3

Answer:

[tex](x,y)=\left(\; \boxed{-3,4} \; \right)\quad \textsf{(smaller $x$-value)}[/tex]

[tex](x,y)=\left(\; \boxed{5,0} \; \right)\quad \textsf{(larger $x$-value)}[/tex]

Step-by-step explanation:

Given system of equations:

[tex]\begin{cases}\;x+2y=5\\x^2+y^2=25\end{cases}[/tex]

To solve by the method of substitution, rearrange the first equation to make x the subject:

[tex]\implies x=5-2y[/tex]

Substitute the found expression for x into the second equation and rearrange so that the equation equals zero:

[tex]\begin{aligned}x=5-2y \implies (5-2y)^2+y^2&=25\\25-20y+4y^2+y^2&=25\\5y^2-20y+25&=25\\5y^2-20y&=0\end{aligned}[/tex]

Factor the equation:

[tex]\begin{aligned}5y^2-20y&=0\\5y(y-4)&=0\end{aligned}[/tex]

Apply the zero-product property and solve for y:

[tex]5y=0 \implies y=0[/tex]

[tex]y-4=0 \implies y=4[/tex]

Substitute the found values of y into the first equation and solve for x:

[tex]\begin{aligned}y=0 \implies x+2(0)&=5\\x&=5\end{aligned}[/tex]

[tex]\begin{aligned}y=4 \implies x+2(4)&=5\\x+8&=5\\x&=-3\end{aligned}[/tex]

Therefore, the solutions are:

[tex](x,y)=\left(\; \boxed{-3,4} \; \right)\quad \textsf{(smaller $x$-value)}[/tex]

[tex](x,y)=\left(\; \boxed{5,0} \; \right)\quad \textsf{(larger $x$-value)}[/tex]

ACCESS MORE